Think Again: the Power of Knowing What You Dont Know - Grant, Adam (UK Penguin Random House, 2023)
Discover how rethinking can lead to excellence at work and wisdom in life. Intelligence is usually seen as the ability to think and learn, but in a rapidly changing world it might matter more that we can rethink and unlearn. Organisational psychologist Adam Grant is an excerpt on opening other people's minds - and our own. As Wharton's top-rated professor and the bestselling author of Originals and Give and Take, he strives to argue like he's right but listen like he's wrong. Think Again invites us to let go of views that are no longer serving us well and prize mental flexibility, humility, and curiosity over foolish consistency. If knowledge is power, knowing what we don't know is wisdom
Include Index Illustration
Keywords: Individual Rethinking